Quinhentos anos de luta pela terra no Caribe - Childs, Matt D. (Afro-Ásia, 2023)
'Resenha de: DUBOIS, Laurent; e TURITS, Richard Lee. Freedom Roots: Histories from the Caribbean. Chapel Hill: University of North Carolina Press, 2022. 395 p.